Incidence and Predictors of Severe Adverse Drug Reaction Among Patients on Antiretroviral Therapy in Tigray, Ethiopia: A Retrospective Cohort Study - Gebremeskel TG; Gebreyowhans D; Gesesew HA; Ward PR (HIV/AIDS: Research and Palliative Care, 2021)
Teferi Gebru Gebremeskel,1 Destalem Gebreyowhans,2 Hailay Abrha Gesesew,3,4 Paul R Ward3 1Department of Reproductive Health, College of Health Sciences, Aksum University, Aksum, Ethiopia; 2School of Medicine, College of Medicine and Health Science, Aksum University, Aksum, Ethiopia; 3Discipline of Public Health, Flinders University, Adelaide, South Australia, Australia; 4Department of Epidemiology, College of Health Sciences, Mekele University, Mekele, EthiopiaCorrespondence: Teferi Gebru Gebremeskel Email teferigebru12@gmail.comBackground: The aim of the present study was to assess the incidence and predictors of severe adverse drug reactions among patients on antiretroviral therapy (ART) in Tigray, North Ethiopia.Methods: We employed four years retrospective cohort study using a structured data extraction sheet. The study populations were HIV patients on ART follow-up from January 2017 to February 2020 in the study area. Severe adverse drug reaction (ADR) was an outcome variable and defined as having any one of the complaints related to ARV drug reaction due to regimen change, discontinuation, and/or in-patient care. Data were collected using a structured data extraction sheet. A Cox proportional hazard regression model was used to determine the relationship between the predictors and the outcome variable. The mean survival time of the cohort was estimated using the Kaplan–Meier method.Results: The incidence rate of ADRs was 3.6 (95%CI: 2.9– 4.35) per 100-person years. HIV patients with no formal education (adjusted hazard ratio=1.58, 95%CI: 1.03– 2.41), with experience of regimen change (adjusted hazard ratio=1.59, 95%CI: 1.12– 2.91), who ever took other medication (adjusted hazard ratio=1.49, 95%CI: 1.05– 2.15) and with lower body mass index (adjusted hazard ratio=3.24, 95%CI: 1.18– 4.91) were more likely to develop severe adverse drug reaction.Conclusion: ADRs were diagnosed an inconsiderable number of HIV patients on ART and factors were patient and drug-related. To minimize it, special attention is sought for patients with no formal education, previous regime change, whoever took other medication, and who have lower body mass index levels.Keywords: human immunodeficiency virus, adverse drug reactions, antiretroviral therapy